Nitrergic neurotransmission in the paraventricular nucleus of the hypothalamus modulates autonomic, neuroendocrine and behavioral responses to acute restraint stress in rats - Busnardo, Cristiane (2019)
We investigated the involvement of nitrergic neurotransmission within the paraventricular nucleus of the hypothalamus (PVN) in modulation of local neuronal activation, autonomic and neuroendocrine responses and behavioral consequences of acute restraint stress in rats. Bilateral microinjections of the selective neuronal nitric oxide (NO) synthase (nNOS) inhibitor N w -Propyl-L-arginine (NPLA) or the NO scavenger carboxy-PTIO into the PVN reduced arterial pressure and heart rate increases, as well as the fall in cutaneous tail temperature induced by restraint stress. PVN injection of either NPLA or carboxy-PTIO also inhibited restraint-induced increases in anxiety-related behaviors in the elevated plus-maze 24 h later. Local microinjection of NPLA or carboxy-PTIO into the PVN reduced the number of c-fos-immunoreactive neurons in the dorsal parvocellular, ventromedial, medial parvocellular and lateral magnocelllular portions of the PVN in animals subjected to restraint stress. However, neither NPLA nor carboxy-PTIO into the PVN affected restraint-induced increases in plasma corticosterone concentration. The present results indicate that PVN nitrergic neurotransmission acting via nNOS activation has a facilitatory influence on autonomic responses to acute restraint and the delayed emotional consequences of restraint stress. Our results also provide evidence of a prominent role of local nitrergic neurotransmission in PVN neuronal activation during stress.